PENERAPAN PENDEKATAN MATEMATIKA REALISTIK INDONESIA (PMRI)UNTUK MENINGKATKAN HASILBELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 030UJUNG TANJUNG KECAMATAN TANAH PUTIH - Is Afrianti Is Afrianti; Otang Kurniaman; Damanhuri Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research have as a starting point of study low result students class III SD Negeri 030Ujung Tanjung Subdistrict Tanah Putih with average class 66,1. While minimize completness criteria value ( KKM ) matematika is 70. From fourteen students, only six peoples that reach out for minimize completness clasical 42,85%. The formulation of problem research is: What application learning cooperative mode type Snowball Trhowing can increase result study matematika students class III SD Negeri 030 Ujung Tanjung Subdistrict Tanah Putih? This research of purpose for increase study result matematika students class III SD Negeri 030 Ujung Tanjung Subdistrict Tanah Putih. This research did of date 28 March until 10 April 2014 with two cycle. Subject this research is students class III SD Negeri 030 UjungTanjung Subdistrict Tanah Putih. Instrument collect data of this skripsi is observation sheet teacher activity and obsevate sheet students activity as study students result. Sheet activity teacher in learning process of cycle one first meet 60,0% (quite category) and second meet increase become 70,0% (good category). Cycle Two firts meet 80,0% (category best good) and second meet increase become 90,0% (best good category). Analiyze result data activity sheet students of cycle one first meet 60,0% (quite category) and second meet become 72,5% (good category). Cycle Two firts meet 77,5% (category good) and second meet is increase become 87,5% (category best good). Study result that before get measure with avarage 66,1. Increase of cycle One with avarage become 73,92 with percentage 11,83%. To cycle two experience increase with average 77,85 with percentage 17,76%. Research result prove that application mode learning cooperatif type Snowball Trhowing can increase result stTudy matematika Students class III SD Negeri 030 Ujung Tanjung Subdistrict Tanah Putih.Key Word : Learning Mathematics Realistic Indonesian, Result Study Matematika.